Determinants of Malaysia’s bilateraltrade in the manufacturing sector: A comparison between China and Asean - Wong, Hueynee; Chin, Muiyin; Teo, Cia Ling; Puah, Chin Hong (International Academy of Business and Economics, 2015)
Malaysia relies heavily on international trade to drive its economic growth. Thus, this study aims to identify the determinants of bilateral trade between Malaysia and its major trading partners, namely, ASEAN-4 (Indonesia, the Philippines, Singapore and Thailand) and China. Both time series and panel models are utilised in this study for the period of 1980-2013. Empirical results show that the determinants for the countries under study are similar. The study finds that the development of human capital in Malaysia plays a pivotal role in enhancing and sustaining the trade ties between Malaysia and its major trading partners